Synthesis, Characterization And Activity Of Mixed Metal Oxide (Mg, Zn, Al) Catalysts For Transesterification Of Waste Cooking Palm Oil, Edible And Non-Edible Oils - Olutoye, Moses Aderemi (2012)

(untitled)
Biodiesel, also known as fatty acid methyl esters (FAME), is an alternative fuel that could be obtained by homogeneous or heterogeneous catalytic processes. It is renewable and its combustion is environment friendly compared to fossil (crude petroleum). This research focused on the development and synthesis of solid catalyst from combination of some metals to produce composite catalyst with KyMg1-xZn1+xAl(2-y)/3O3 (at y = 0 and 0.1≤ x ≤0.9) suitable to produce FAME from different vegetable oils-edible and non-edible sources (refined palm oil (RPO), waste cooking palm oil (WCPO), coconut oil (CCO), palm kernel oil (PKO) and crude jatropha oil (CJO)) most specifically from palm oil since Malaysia is one of the world’s largest producer and it’s available in commercial quantity.